A METHODOLOGICAL PERSPECTIVE TO ENHANCE BASKETBALL PLAYERS’ PHYSICAL EDUCATION - Singh, Gurdeep; Singh, Jaswinder (International Journal of Psychosocial Rehabilitation, 2021)
It is via the design of the tasks that students are subjected to physical and physiological demands that their physical fitness is determined by the teacher’s technique in Physical Education classes. As a way to examine the impact of three distinct teaching approaches on students’ basketball skills, this study compared the external and internal loads (eTL and iTL) of the Tactical Games Approach (TGA), Direct Instruction (DI) and Service Teacher’s Basketball Unit (STBU). Researchers also looked at the ratings of perceived exertion (RPE) from the evaluations (before and after). A total of 49 kids, ranging in age from 11 to 12, from a state school in Spain’s sixth grade participated in the study. Students were divided into groups and given teaching-learning packages at random. Inertial devices were used to capture physical activity and transform it into kinetic characteristics for each session. Students who used the TGA approach had greater eTL (player load; DI = 4.92, TGA = 6.95, STBU = 2.99) and iTL (internal load) readings during the sessions. During the evaluations, their heart rates were comparable to those of students in other programmes. They also passed. High-intensity exercise, such as running (DI = 3.42, TGA = 11.26, STBU = 8.32) and sprinting (DI= 0.00, TGA = 0.12, STBU = 0.11), was more prevalent in their daily routines, despite the fact that they were less physically fit. Students with little prior basketball experience had greater peak speeds, whereas more experienced players had higher heart rates throughout the evaluations. Because it favours primary school children’s physical health and well-being, the TGA technique is frequently cited in the design of Physical Education lessons